Record of mother-calf pair of southern right whales (Eubalaena australis) off the coast of Lima, Peru - Orihuela, Mariana (2013)
Before this report, the distribution in the South Eastern Pacific of the Southern Right whales was knew until to 15°08’S in San Fernando Bay, Ica. Previously, southern right whales in Perú were recorded in November 1987 in Ilo, Moquegua and September 1996 in Atico, Arequipa. These records could show the possible recovery in the southeastern Pacific of the right whale population, which has been declared Critically Endangered by the IUCN. We reported a mother-calf pair sighting on August 20, 2012 in Chorrillos district, Lima from 9:30 h to 13:30 h for 4 hours.